Poster presentations in Translation Studies: State of the art and seven tips for improvement - Laura Ivaska; Ester Torres-Simón (Finland, 2022)
Poster presentations have established themselves in hard and social sciences, but remain an undervalued asset in Translation Studies (TS). In this paper, we report on a survey (n=104) that we carried out to map TS scholars’ behavior and preferences regarding poster and oral presentations in conferences. Based on the results, we argue that the full potential of posters as a tool for disseminating research results, getting feedback and networking with colleagues has not been realized in TS. Although the role of posters in facilitating these interactions is acknowledged in the survey responses, the results also reveal that poster presenters are often underprepared: they have not studied making posters nor do they rehearse presenting the poster beforehand. Having identified this lack of preparation, we provide tips for making and presenting engaging posters. In addition, we discuss issues that conference organizers could pay attention to when organizing poster sessions. We hope to encourage more TS scholars to present posters in future conferences by suggesting that the visuality of posters can be harnessed to attract new audiences and to initiate meaningful interactions.